3,6-Carbazole vs 2,7-carbazole: A comparative study of hole-transporting polymeric materials for inorganic–organic hybrid perovskite solar cells - Li, Wei; Otsuka, Munechika; Kato, Takehito; Wang, Yang; Mori, Takehiko; Michinobu, Tsuyoshi (Beilstein Journal of Organic Chemistry, 2016)
The ever increasing demand for clean energy has encouraged researchers to intensively investigate environmentally friendly photovoltaic devices. Inorganic–organic hybrid perovskite solar cells (PSCs) are very promising due to their potentials of easy fabrication processes and high power conversion efficiencies (PCEs). Designing hole-transporting materials (HTMs) is one of the key factors in achieving the high PCEs of PSCs. We now report the synthesis of two types of carbazole-based polymers, namely 3,6-Cbz-EDOT and 2,7-Cbz-EDOT, by Stille polycondensation. Despite the same chemical composition, 3,6-Cbz-EDOT and 2,7-Cbz-EDOT displayed different optical and electrochemical properties due to the different connectivity mode of the carbazole unit. Therefore, their performances as hole-transporting polymeric materials in the PSCs were also different. The device based on 2,7-Cbz-EDOT showed better photovoltaic properties with the PCE of 4.47% than that based on 3,6-Cbz-EDOT. This could be due to its more suitable highest occupied molecular orbital (HOMO) level and higher hole mobility.
Keywords: carbazole polymer; hole transport; perovskite solar cell; polycondensation

(untitled) - Kojima, A.; Teshima, K.; Shirai, Y.; Miyasaka, T. (J. Am. Chem. Soc., 2009)

(untitled) - Liu, M.; Johnston, M. B.; Snaith, H. J. (Nature, 2013)

(untitled) - Zhou, H.; Chen, Q.; Li, G.; Luo, S.; Song, T.-b.; Duan, H.-S.; Hong, Z.; You, J.; Liu, Y.; Yang, Y. (Science, 2014)

(untitled) - Rakstys, K.; Abate, A.; Dar, M. I.; Gao, P.; Jankauskas, V.; Jacopin, G.; Kamarauskas, E.; Kazim, S.; Ahmad, S.; Grätzel, M.; Nazeeruddin, M. K. (J. Am. Chem. Soc., 2015)

(untitled) - Huang, C.; Fu, W.; Li, C.-Z.; Zhang, Z.; Qiu, W.; Shi, M.; Heremans, P.; Jen, A. K.-Y.; Chen, H. (J. Am. Chem. Soc., 2016)

(untitled) - Jeon, N. J.; Lee, J.; Noh, J. H.; Nazeeruddin, M. K.; Grätzel, M.; Seok, S. I. (J. Am. Chem. Soc., 2013)

(untitled) - Bi, D.; Yang, L.; Boschloo, G.; Hagfeldt, A.; Johansson, E. M. J. (J. Phys. Chem. Lett., 2013)

(untitled) - Margulis, G. Y.; Christoforo, M. G.; Lam, D.; Beiley, Z. M.; Bowring, A. R.; Bailie, C. D.; Salleo, A.; McGehee, M. D. (Adv. Energy Mater., 2013)

(untitled) - Jeon, N. J.; Lee, H. G.; Kim, Y. C.; Seo, J.; Noh, J. H.; Lee, J.; Seok, S. I. (J. Am. Chem. Soc., 2014)

(untitled) - Liu, J.; Pathak, S.; Stergiopoulos, T.; Leijtens, T.; Wojciechowski, K.; Schumann, S.; Kausch-Busies, N.; Snaith, H. J. (J. Phys. Chem. Lett., 2015)

(untitled) - Di Giacomo, F.; Razza, S.; Matteocci, F.; D'Epifanio, A.; Licoccia, S.; Brown, T. M.; Di Carlo, A. (J. Power Sources, 2014)

(untitled) - Kwon, Y. S.; Lim, J.; Yun, H.-J.; Kim, Y.-H.; Park, T. (Energy Environ. Sci., 2014)

(untitled) - Ryu, S.; Noh, J. H.; Jeon, N. J.; Kim, Y. C.; Yang, W. S.; Seo, J.; Seok, S. I. (Energy Environ. Sci., 2014)

(untitled) - Grazulevicius, J. V.; Strohriegl, P.; Pielichowski, J.; Pielichowski, K. (Prog. Polym. Sci., 2003)

(untitled) - Morin, J.-F.; Leclerc, M.; Adès, D.; Siove, A. (Macromol. Rapid Commun., 2005)

(untitled) - Blouin, N.; Leclerc, M. (Acc. Chem. Res., 2008)

(untitled) - Li, J.; Grimsdale, A. C. (Chem. Soc. Rev., 2010)

(untitled) - Beaupré, S.; Boudreault, P.-L. T.; Leclerc, M. (Adv. Mater., 2010)

(untitled) - Boudreault, P.-L. T.; Beaupré, S.; Leclerc, M. (Polym. Chem., 2010)

(untitled) - Wong, W.-Y.; Harvery, R. D. (Macromol. Rapid Commun., 2010)

(untitled) - Beaupré, S.; Leclerc, M. (J. Mater. Chem. A, 2013)

(untitled) - Tao, X.-T.; Zhang, Y.-D.; Wada, T.; Sasabe, H.; Suzuki, H.; Watanabe, T.; Miyata, S. (Adv. Mater., 1998)

(untitled) - Michinobu, T.; Okoshi, K.; Osako, H.; Kumazawa, H.; Shigehara, K. (Polymer, 2008)

(untitled) - Cai, B.; Xing, Y.; Yang, Z.; Zhang, W.-H.; Qiu, J. (Energy Environ. Sci., 2013)

(untitled) - Dumur, F. (Org. Electron., 2015)

(untitled) - Morin, J.-F.; Leclerc, M. (Macromolecules, 2001)

(untitled) - Dierschke, F.; Grimsdale, A. C.; Müllen, K. (Synthesis, 2003)

(untitled) - Blouin, N.; Michaud, A.; Wakim, S.; Boudreault, P.-L. T.; Leclerc, M.; Vercelli, B.; Zecchin, S.; Zotti, G. (Macromol. Chem. Phys., 2006)

(untitled) - Leclerc, N.; Michaud, A.; Sirois, K.; Morin, J.-F.; Leclerc, M. (Adv. Funct. Mater., 2006)

(untitled) - Blouin, N.; Michaud, A.; Gendron, D.; Wakim, S.; Blair, E.; Neagu-Plesu, R.; Belletête, M.; Durocher, G.; Tao, Y.; Leclerc, M. (J. Am. Chem. Soc., 2008)

(untitled) - Aïch, R. B.; Blouin, N.; Bouchard, A.; Leclerc, M. (Chem. Mater., 2009)

(untitled) - Michinobu, T.; Kumazawa, H.; Otsuki, E.; Usui, H.; Shigehara, K. (J. Polym. Sci., Part A: Polym. Chem., 2009)

(untitled) - Ma, Z.; Chen, L.; Ding, J.; Wang, L.; Jing, X.; Wang, F. (Adv. Mater., 2011)

(untitled) - Hahm, S. G.; Lee, T. J.; Kim, D. M.; Kwon, W.; Ko, Y.-G.; Michinobu, T.; Ree, M. (J. Phys. Chem. C, 2011)

(untitled) - Lombeck, F.; Komber, H.; Sepe, A.; Friend, R. H.; Sommer, M. (Macromolecules, 2015)

(untitled) - Berns, B.; Tieke, B. (Polym. Chem., 2015)

(untitled) - Li, W.; Michinobu, T. (Polym. Chem., 2016)
Note that 3, 6-Cbz-EDOT was previously synthesized by direct arylation polycondensation.

(untitled) - Bucinskas, A.; Bagdziunas, G.; Tomkeviciene, A.; Volynyuk, D.; Kostiv, N.; Gudeika, D.; Jankauskas, V.; Rutkis, M.; Grazulevicius, J. V. (RSC Adv., 2015)

(untitled) - Zhu, Z.; Bai, Y.; Lee, H. K. H.; Mu, C.; Zhang, T.; Zhang, L.; Wang, J.; Yan, H.; So, S. K.; Yang, S. (Adv. Funct. Mater., 2014)

(untitled) - Cho, S.; Seo, J. H.; Park, S. H.; Beaupré, S.; Leclerc, M.; Heeger, A. J. (Adv. Mater., 2010)

(untitled) - Huang, C.; Sartin, M. M.; Cozzuol, M.; Siegel, N.; Barlow, S.; Perry, J. W.; Marder, S. R. (J. Phys. Chem. A, 2012)

(untitled) - Kim, J. Y.; Kim, S. H.; Lee, H.-H.; Lee, K.; Ma, W.; Gong, X.; Heeger, A. J. (Adv. Mater., 2006)

(untitled) - Dubey, A.; Adhikari, N.; Venkatesan, S.; Gu, S.; Khatiwada, D.; Wang, Q.; Mohammad, L.; Kumar, M.; Qiao, Q. (Sol. Energy Mater. Sol. Cells, 2016)

(untitled) - Chen, W.; Bao, X.; Zhu, Q.; Zhu, D.; Qiu, M.; Sun, M.; Yang, R. (J. Mater. Chem. C, 2015)

(untitled) - Bisquert, J.; Bertoluzzi, L.; Mora-Sero, I.; Garcia-Belmonte, G. (J. Phys. Chem. C, 2014)

(untitled) - Juarez-Perez, E. J.; Wußler, M.; Fabregat-Santiago, F.; Lakus-Wollny, K.; Mankel, E.; Mayer, T.; Jaegermann, W.; Mora-Sero, I. (J. Phys. Chem. Lett., 2014)

(untitled) - Zhang, J.; Hu, Z.; Huang, L.; Yue, G.; Liu, J.; Lu, X.; Hu, Z.; Shang, M.; Han, L.; Zhu, Y. (Chem. Commun., 2015)

(untitled) - Xiao, Y.; Han, G.; Wu, J.; Lin, J.-Y. (J. Power Sources, 2016)

(untitled) - Jung, S.-H.; Kim, H. K.; Kim, S.-H.; Kim, Y. H.; Jeoung, S. C.; Kim, D. (Macromolecules, 2000)

(untitled) - Li, W.; Michinobu, T. (Macromol. Chem. Phys., 2016)